Loss of Dnmt3a increases self-renewal and resistance to pegIFN-α in JAK2-V617F-positive myeloproliferative neoplasms - Usart, Marc; Stetka, Jan; Luque Paz, Damien; Hansen, Nils; Kimmerlin, Quentin; Almeida Fonseca, Tiago; Lock, Melissa; Kubovcakova, Lucia; Karjalainen, Riikka; Hao-Shen, Hui; Börsch, Anastasiya; El Taher, Athimed; et al. (Blood, 2024)
Pegylated interferon alfa (pegIFN-α) can induce molecular remissions in patients with JAK2-V617F-positive myeloproliferative neoplasms (MPNs) by targeting long-term hematopoietic stem cells (LT-HSCs). Additional somatic mutations in genes regulating LT-HSC self-renewal, such as DNMT3A, have been reported to have poorer responses to pegIFN-α. We investigated whether DNMT3A loss leads to alterations in JAK2-V617F LT-HSC functions conferring resistance to pegIFN-α treatment in a mouse model of MPN and in hematopoietic progenitors from patients with MPN. Long-term treatment with pegIFN-α normalized blood parameters and reduced splenomegaly and JAK2-V617F chimerism in single-mutant JAK2-V617F (VF) mice. However, pegIFN-α in VF;Dnmt3aΔ/Δ (VF;DmΔ/Δ) mice worsened splenomegaly and failed to reduce JAK2-V617F chimerism. Furthermore, LT-HSCs from VF;DmΔ/Δ mice compared with VF were less prone to accumulate DNA damage and exit dormancy upon pegIFN-α treatment. RNA sequencing showed that IFN-α induced stronger upregulation of inflammatory pathways in LT-HSCs from VF;DmΔ/Δ than from VF mice, indicating that the resistance of VF;DmΔ/Δ LT-HSC was not due to failure in IFN-α signaling. Transplantations of bone marrow from pegIFN-α-treated VF;DmΔ/Δ mice gave rise to more aggressive disease in secondary and tertiary recipients. Liquid cultures of hematopoietic progenitors from patients with MPN with JAK2-V617F and DNMT3A mutation showed increased percentages of JAK2-V617F-positive colonies upon IFN-α exposure, whereas in patients with JAK2-V617F alone, the percentages of JAK2-V617F-positive colonies decreased or remained unchanged. PegIFN-α combined with 5-azacytidine only partially overcame resistance in VF;DmΔ/Δ mice. However, this combination strongly decreased the JAK2-mutant allele burden in mice carrying VF mutation only, showing potential to inflict substantial damage preferentially to the JAK2-mutant clone.
Keywords: myeloproliferativní poruchy; Cell Self Renewal; interferon alfa; rekombinantní proteiny; myši inbrední C57BL; Mice, Inbred C57BL; Janus Kinase 2; DNA Methyltransferase 3A; Mice; DNA methyltransferasa 3A; Polyethylene Glycols; polyethylenglykoly; Interferon-alpha; Myeloproliferative Disorders; chemorezistence; zvířata; DNA-(cytosin-5-)methyltransferasa; Humans; Drug Resistance, Neoplasm; buněčná sebeobnova; DNA (Cytosine-5-)-Methyltransferases; myši; hematopoetické kmenové buňky; Hematopoietic Stem Cells; Janus kinasa 2; lidé; Recombinant Proteins; Animals